Design And Development Of 2-In-1 Automatic Pet Feeder - Lim, Joe Yin
Automatic pet feeder is one of the new technologies that assist the pet owners to feed their pets according to schedule. Nowadays, people loves to keep pets at home. However, some of the pet owners tend to forget to feed their pets. 2-in-1 automatic pet feeder is a programmable feeder which helps the pet owners to make sure that their pets have access an amount of food throughout the day. There are two systems in the feeder, which are food system and water system, where they work alternatively. The feeder is designed and programmed by using SolidWorks and Arduino software. In the first phase of the project, customers’ needs are identified to establish the specifications and criteria of the product. In the design stage, four concepts of the product are generated. The finalized concept is chosen by analyzing the data collected in concept testing survey. Concept C is chosen as the finalized criteria and specifications of the product as it has higher market potential, which is 0.2666666667 compared to that of concept D, 0.2380952381. A new concept is designed based on the specification of concept C. An economic analysis is built to compute the net present value of the product. Unit production cost of the product is estimated as RM360 per unit and the unit price is RM560 per unit. The net present value calculated for four years is RM 3,099,000. This project can be used to support major investment as it has a positive value of net present value. A prototype of the product is built by using Medium Density Fiberboard, cardboard, and electronic components. After all the stages, demonstration and functionality test are run as the feeder able to release food and water accordingly.